Análise de metodologia de melhoria de processos: aplicações à indústria automobilística - Dias, Elder Emanoel Pedrosa (2007)
This dissertation proposes a model for a Methodology of Analysis and Improvement of the Process (MAMP) with integrated use of the Quality Tools. The methodology consists of a series of steps in a logical sequence that allow to analyze, identify and propose solutions for the quality problems. Actually the MAMP proposed in this dissertation it is an improved adaptation of the Problems and Solution Process of DaimlerChrysler Brazil, which is used in Juiz de Fora plant. Along the preparation of this dissertation a revision of the literature has been made as well as a search of the main attributes (criteria) of MAMP. The steps of the methodology were developed making use of the most appropriate quality tools for the execution of each stage. Also it has been made a practical application of the proposed Methodology, where satisfactory results have been reached for the improvement of the quality, for the manufacturing processes and, consequently, for the finished product. This way a shorter time for problems analysis and a cost rework reduction have been noted as well as the enterprise s goals have been met